Lanthanum carbonate oral powder: satisfaction, preference and adherence in French and Spanish patients with end-stage renal disease - Michael Keith; Patricia de Sequera; Francois Clair; Riccardo Pedersini (BioExcel Publishing Ltd, 2016)
Background: Phosphate binders, such as lanthanum carbonate, control elevated serum-phosphate levels in patients with end-stage renal disease (ESRD). Lanthanum carbonate is available in oral powder and tablet form. The aim of this survey was to investigate satisfaction with, preference for, and adherence to lanthanum carbonate oral powder in patients with ESRD. Scope: Patients from France and Spain who had been taking lanthanum carbonate powder for at least 4 weeks, and who had experience of other phosphate binders of any formulation, were asked to complete an online or telephone survey. Treatment satisfaction was measured using the Treatment Satisfaction Questionnaire for Medication-9; preference was measured using 5-point Likert scale agreement ratings; and adherence was measured using the Morisky Medication Adherence Scale-4. Data were evaluated using bivariate analyses. Findings: Overall, 160 patients participated (80 per country). Lanthanum carbonate powder was reported to have a higher effectiveness rating (p<0.05), be more convenient (p<0.05), and provide a higher level of satisfaction (p<0.01) than previous binders. There was an overall preference for lanthanum carbonate powder over previous binders of any formulation (p<0.001). Adherence to medication was similar for all binders analysed: 66.3% of French patients adhered to lanthanum carbonate powder, and 65.0% adhered to previous binder treatment (p=not significant); 52.5% of Spanish patients adhered to lanthanum carbonate powder, and 56.3% adhered to previous binder treatment (p=not significant). Limitations: The survey enrolled patients who had already experienced phosphate binders before the study began. Information on patient preferences for and adherence to previous phosphate binders was therefore based on the patients' memories of these experiences, which may have been subject to change over time. Although most participants completed the online survey in this study, a telephone survey was used for individuals who could not access the online version; if only one method of data recording had been used, there may have been reduced variation in responses. Conclusion: Patients with ESRD report increased satisfaction with and preference for lanthanum carbonate powder over other formulations, suggesting that lanthanum carbonate powder is more convenient and easier to use than other formulations.